Determinants of stock return in 10 biggest market capitalization on the indonesian stock exchange - Sri Yanthy Yosepha; Kampono Imam Yulianto; Zulfitra Zulfitra; Sahroni Sahroni; Luqman Hakim (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Several research results on the capital market in Indonesia fall into the category of market efficiency in the weak form, so the results of previous research do not reflect the theory of capital market efficiency in the strong form. The purpose of this research is to analyze and answer the existence of inconsistencies in the results of previous research as well as the phenomenon of stock returns which are not as described in capital market theory in strong form. This is what prompted researchers to do it again using different time series and cross-sectional data. This type of research is quantitative descriptive with a panel data multiple regression analysis method using 10 sample companies that are members of 50 large capitalization companies for 7 years. This research formula is to maximize the Stock Return value through leverage as an intervening variable using research objects of companies on the Indonesia Stock Exchange. Two research models are integrated into one and each goes through a model selection test stage, namely the Chow Test, Hausman Test, and Lagrange Multiplier Test using the eviews12 application. The results of this research explain that increasing ROA can have an impact on reducing Leverage (DER) and through DER it can explain the impact on Stock Returns, but ROA cannot directly explain Stock Returns. It is hoped that these results can help as a guide for investors to get maximum Stock Returns.